2017
DOI: 10.1016/s2352-4642(17)30051-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of community-based support for caregivers on the risk of virological failure in children and adolescents with HIV in Harare, Zimbabwe (ZENITH): an open-label, randomised controlled trial

Abstract: SummaryBackgroundChildren and adolescents have poorer HIV treatment outcomes than adults. We aimed to assess the effect of community-based support for caregivers of HIV-infected children and adolescents, who are key mediators to children engaging with care, on treatment outcomes.MethodsIn this open-label, randomised contolled trial, we recruited children aged 6–15 years with newly-diagnosed HIV attending primary health-care clinics in Harare, Zimbabwe. Children were randomly assigned to receive decentralised p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 27 publications
1
72
1
Order By: Relevance
“…These silences highlight the relative disempowerment and limited agency of adolescents, especially among females, in discussing this aspect of their lives . In addition, our findings also align with a growing understanding that some caregivers need additional support to care for ALHIV , and that such interventions may be best delivered outside of the clinic, through home visits . Such initiatives need to acknowledge the inter‐generational conflicts that are often commonplace within homes, and that parenting interventions beyond those focusing on adherence may be needed .…”
Section: Discussionsupporting
confidence: 71%
“…These silences highlight the relative disempowerment and limited agency of adolescents, especially among females, in discussing this aspect of their lives . In addition, our findings also align with a growing understanding that some caregivers need additional support to care for ALHIV , and that such interventions may be best delivered outside of the clinic, through home visits . Such initiatives need to acknowledge the inter‐generational conflicts that are often commonplace within homes, and that parenting interventions beyond those focusing on adherence may be needed .…”
Section: Discussionsupporting
confidence: 71%
“…For future studies that are conducted in low‐resource settings such as this one, where viral load testing is rare and inconsistent, it may be of value to conduct independent viral load assessments. These limitations reflect some of the challenges of conducting research within real‐world public health services in Africa, outside high‐quality teaching hospitals and donor‐funded clinics . This study uses self‐reported clinic non‐attendance and ART non‐adherence, which risk recall and social desirability biases.…”
Section: Discussionmentioning
confidence: 99%
“…They also suggest that economic and psychosocial services may be valuable in supporting health system use and treatment adherence . Two ongoing randomized trials in South Africa and Uganda examine family‐based and economic strengthening approaches to adherence support, and successful pilots suggest likely positive impacts .…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, existing models have focused on clinically stable families and children with reliable caregivers, and knowledge gaps exist regarding models for at‐risk families . Psychosocial interventions that address stigma, disclosure and mental health issues will likely play an important role in these models .…”
Section: Discussionmentioning
confidence: 99%